2015
DOI: 10.1093/bja/aeu293
|View full text |Cite
|
Sign up to set email alerts
|

Impact of pregabalin on acute and persistent postoperative pain: a systematic review and meta-analysis

Abstract: We performed this systematic review to assess the analgesic efficacy of perioperative pregabalin. Subgroup analyses and meta-regression were performed to assess the impact of individual dose and frequency of pregabalin administration on analgesic efficacy. We included 55 studies. When all doses and administration regimens were combined, pregabalin was associated with a significant reduction in pain scores at rest and during movement and opioid consumption at 24 h compared with placebo {mean difference [95% con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
241
3
9

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 304 publications
(267 citation statements)
references
References 69 publications
14
241
3
9
Order By: Relevance
“…115 However, these often report a low proportion of variation explained when compared to our results using baseline risk.…”
Section: Discussioncontrasting
confidence: 69%
“…115 However, these often report a low proportion of variation explained when compared to our results using baseline risk.…”
Section: Discussioncontrasting
confidence: 69%
“…Pregabalin is a drug which binds to Ca 2+ channels in nerve presynapses, suppressing the release of neurotransmitters and resulting in an analgesic effect (19)(20)(21)(22)(23). There have been many reports showing excellent efficacy of pregabalin against neuropathic pain and postoperative pain (29)(30)(31)(32).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the development of a safe pain management alternative to Original Article Impact of pregabalin on early phase post-thoracotomy pain compared with epidural analgesia epidural analgesia which can be administered for extended periods of time is desirable. Pregabalin is a therapeutic drug for neuropathic pain which interacts with presynapses and would be anticipated to show an effect similar to epidural analgesia (19)(20)(21)(22)(23). We have reported that pregabalin is effective against post-thoracotomy pain (24)(25)(26).…”
Section: Introductionmentioning
confidence: 99%
“…Our findings regarding preoperative anxiety was that there was significantly lower anxiety with pregabalin. Regarding persistent pain, the benefits after 3 months was non conclusive, whereas at 6 and 12 months, there was little benefit [2,3]. The optimal dose or frequency of administration of pregabalin ranged from 50 to 300 mg. We found the drug dosage of 100 -150 and 300 mg but not ≤75 mg at 2 hours after surgery, whereas at 24 hours, no statistically significant differences were detected between the three dose levels.…”
Section: Discussionmentioning
confidence: 99%
“…It is usually prescribed for postoperative pain management [1,2].Several studies have been carried out to evaluate the efficacy of perioperative pregabalin in doses 50 to 300 mg. All the studies showed better postoperative analgesia after adminstration of pregabalin [3][4][5].Few studies used 300 mg of pregabalin and others used in the range of 50-150, 225-300, and 600-750 mg, but whether effects of the drug is due to its dosage or frequency of administration is not yet clear. Several studies investigated role of perioperative pregabalin in relieving acute pain.…”
Section: Introductionmentioning
confidence: 99%